Comparative Evaluation of Radioiodine and Technetium-Labeled DARPin 9_29 for Radionuclide Molecular Imaging of HER2 Expression in Malignant Tumors. (6th June 2018) - Vorobyeva, Anzhelika; Bragina, Olga; Altai, Mohamed; Mitran, Bogdan; Orlova, Anna; Shulga, Alexey; Proshkina, Galina; Chernov, Vladimir; Tolmachev, Vladimir; Deyev, Sergey
Abstract : High expression of human epidermal growth factor receptor 2 (HER2) in breast and gastroesophageal carcinomas is a predictive biomarker for treatment using HER2-targeted therapeutics (antibodies trastuzumab and pertuzumab, antibody-drug conjugate trastuzumab DM1, and tyrosine kinase inhibitor lapatinib). Radionuclide molecular imaging of HER2 expression might permit stratification of patients for HER2-targeting therapies. In this study, we evaluated a new HER2-imaging probe based on the designed ankyrin repeat protein (DARPin) 9_29. DARPin 9_29 was labeled with iodine-125 by direct radioiodination and with [ 99m Tc]Tc(CO)3 using the C-terminal hexahistidine tag. DARPin 9_29 preserved high specificity and affinity of binding to HER2-expressing cells after labeling. Uptake of [ 125 I]I-DARPin 9_29 and [ 99m Tc]Tc(CO)3 -DARPin 9_29 in HER2-positive SKOV-3 xenografts in mice at 6 h after injection was 3.4 ± 0.7 %ID/g and 2.9 ± 0.7 %ID/g, respectively. This was significantly (p < 0.00005 ) higher than the uptake of the same probes in HER2-negative Ramos lymphoma xenografts, 0.22 ± 0.09 %ID/g and 0.30 ± 0.05 %ID/g, respectively. Retention of [ 125 I]I-DARPin 9_29 in the lung, liver, spleen, and kidneys was appreciably lower compared with [ 99m Tc]Tc(CO)3 -DARPin 9_29, which resulted in significantly (p < 0.05 ) higher tumor-to-organ ratios. The biodistribution data were confirmed by SPECT/CT imaging. In conclusion, radioiodine is a preferable label for DARPin 9_29.